2019
DOI: 10.1377/hlthaff.2018.05495
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty About DACA May Undermine Its Positive Impact On Health For Recipients And Their Children

Abstract: Undocumented immigrants and their children have worse selfreported health than documented immigrants and US citizens do. Evidence suggests that the Deferred Action for Childhood Arrivals (DACA) program, which was created in 2012 by President Barack Obama and which granted some rights to undocumented immigrants who arrived as children, improved the well-being of recipients and their children in the first three years after the program's introduction. However, DACA is subject to executive discretion, and the US p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 28 publications
3
48
0
Order By: Relevance
“…A number of studies have examined the short-term impacts of DACA for eligible immigrants. These studies find overwhelmingly positive effects of DACA in the two-to-three years following its passage, including increased high school completion (Hamilton, Patler and and improvements to health and mental health for both DACA recipients and their children (Hainmueller et al 2017, Patler and Pirtle 2018, Patler et al 2019, Venkataramani et al 2017).…”
Section: Undocumented Youth Daca and Legal Transitionsmentioning
confidence: 99%
“…A number of studies have examined the short-term impacts of DACA for eligible immigrants. These studies find overwhelmingly positive effects of DACA in the two-to-three years following its passage, including increased high school completion (Hamilton, Patler and and improvements to health and mental health for both DACA recipients and their children (Hainmueller et al 2017, Patler and Pirtle 2018, Patler et al 2019, Venkataramani et al 2017).…”
Section: Undocumented Youth Daca and Legal Transitionsmentioning
confidence: 99%
“…For instance, populations targeted by the Trump administration are likely to feel the stress effects of being targeted by rhetoric in the public sphere and media. These populations will also likely suffer stress and health effects based on having their rights curtailed, or in anticipation of having their rights curtailed, through legislation or policy (Hatzenbuehler, ; Hoyt, Zeiders, Chaku, Toomey, & Nair, ; Patler, Hamilton, Meagher, & Savinar, ; Williams & Medlock, ). For instance, two policies of the Trump administration that are especially likely to be linked to negative health outcomes are the 2017 repeal of DACA and the ongoing separation of families at the border between the US and Mexico (Bouza et al, ; Hainmueller et al, ; MacKenzie et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, two policies of the Trump administration that are especially likely to be linked to negative health outcomes are the 2017 repeal of DACA and the ongoing separation of families at the border between the US and Mexico (Bouza et al, ; Hainmueller et al, ; MacKenzie et al, ). Previous research has assessed the health impacts of the DACA, and its repeal, (Hainmueller et al, ; Mallet & Bedolla, ; Patler et al, ) and family separation (Bouza et al, ; MacKenzie et al, ) and has demonstrated the negative health effects of both policies in the Latino, immigrant, and Latino immigrant populations, and especially for children.…”
Section: Resultsmentioning
confidence: 99%
“…DACA is associated with improvements in the economic, social, and psychological well‐being of recipients relative to nonrecipients (Gonzales et al ; Patler and Pirtle ). Yet, prior to Donald Trump's election and the growing uncertainty surrounding his eventual revocation of DACA (Patler et al ), Marina reported in 2015 having felt more secure without DACA protections than with them. Presciently, she describes an unpredictable political landscape as informing her perceptions: “This is something temporary.…”
Section: System Embeddedness: Perceived Regime Legibility and Deportamentioning
confidence: 99%